Exposição ao fungicida mancozeb resulta em estresse oxidativo como mecanismo comum de toxicidade entre invertebrados e vertebrados aquáticos - Leandro, Luana Paganotto (2024)
Mancozeb (MZ) is widely used as a fungicide in Brazil due to its effectiveness in combating fungal infections in plantations. However, its toxicity to non-target organisms, including aquatic organisms, has been reported in the literature. Recently, Brazilian legislation was updated to allow a concentration of 8 μg/L of MZ in drinking water (Ordinance GM/MS nº 888, of May 4, 2021). However, the safety of this concentration for aquatic organisms has not yet been put to the test. To address this gap, we conducted a study using zebrafish (Danio rerio) embryos at 4 hpf exposed to MZ at the concentration allowed by law, as well as slightly higher sublethal concentrations (24, 72, and 180 μg/L), alongside a control group. Our results showed that the concentration of 8 μg/L, currently permitted in drinking water according to Brazilian legislation, increased ROS production levels and caused alterations in mitochondrial physiology. Among the markers assessed, mitochondrial bioenergetic function appeared to be the most sensitive indicator of MZ embryotoxicity, as a decrease in complex I activity was observed at concentrations of 8 and 180 μg/L. Furthermore, concentrations higher than 8 μg/L impaired morphophysiological markers. Based on these findings, we can infer that the concentration of MZ allowed in drinking water by Brazilian environmental legislation is not safe for aquatic organisms. Furthermore, by comparing effects across organisms of varying complexity, we aim to identify potential common mechanisms of MZ toxicity. A critical literature search yielded 32 articles investigating the effects of MZ and its formulations on diverse aquatic species. Exposure to MZ resulted in a range of toxic effects, including morphophysiological, biochemical, genotoxic, and neurotoxic disruptions in mollusks, crustaceans, aquatic insects, fish, and amphibians. Biochemical effects were the most frequently reported, with MZ primarily targeting mitochondria, lipids, proteins, and genetic material. Notably, the mechanisms underlying MZ-induced neurotoxicity remain poorly understood, representing 31 a significant knowledge gap. Based on the analyzed effects, oxidative stress appears as a potential unifying mechanism of MZ toxicity in both aquatic invertebrates and vertebrates. However, further research is needed to definitively establish a common mechanism and elucidate the specific pathways involved. Additionally, a deeper understanding of MZ neurotoxic effects is crucial for a comprehensive environmental risk assessment.